2012
DOI: 10.1111/j.1365-2672.2012.05299.x
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic and phenotypic characterization of Bordetella pertussis strains used in different vaccine formulations in Latin America

Abstract: Aim:  To characterize Bordetella pertussis vaccine strains in comparison with current circulating bacteria. Methods and Results:  Genomic and proteomic analyses of Bp137 were performed in comparison with other vaccine strains used in Latin America (Bp509 and Bp10536) and with the clinical Argentinean isolate Bp106. Tohama I strain was used as reference strain. Pulse‐field gel electrophoresis (PFGE) and pertussis toxin promoter (ptxP) sequence analysis revealed that Bp137 groups with Bp509 in PFGE group III and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 42 publications
1
19
0
Order By: Relevance
“…3 ), with ptxP 3- ptxA 1- prn 2- fim 3-1 being the more prevalent genotype—it having been designated by other authors as MT27a [ 40 ]. The results detected for fim alleles were similar to those reported for the Argentine isolates fim 2-1 (97 % of those studied), and fim3-2 (76 %) [ 33 ].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…3 ), with ptxP 3- ptxA 1- prn 2- fim 3-1 being the more prevalent genotype—it having been designated by other authors as MT27a [ 40 ]. The results detected for fim alleles were similar to those reported for the Argentine isolates fim 2-1 (97 % of those studied), and fim3-2 (76 %) [ 33 ].…”
Section: Discussionsupporting
confidence: 86%
“…DNA sequencing of B. pertussis genomic regions ( ptx P, ptx A, fim 2, fim , and prn ) was performed with the primers listed in the Table 1 , and according to the protocols of reference [ 33 ]. The PCR products in an agarose gel were purified with QIAquick Gel Extraction Kit (QIAGEN) and the sequencing reaction carried out with the BigDye Terminator v. 3.1 (Applied Biosystems) precipitated and resuspended in Hi-Di formamide (Life Technologies).…”
Section: Methodsmentioning
confidence: 99%
“…Within a timeframe of 10 years, ptxP3 strains have nearly completely replaced the previously dominant ptxP1 strains. Significantly, ptxP3 strains have spread globally, as they have emerged in several countries in Europe [13][17], North America [18], South America [19], and Australia [20]. Phylogenetic analyses showed that ptxP3 strains evolved from ptxP1 strains, possibly in the 1970s [21], [22].…”
Section: Introductionmentioning
confidence: 99%
“…The genomes of the currently circulating Bordetella pertussis isolates differ from the isolates used in the manufacture of vaccine components (8)(9)(10)(11)(12). Allelic variations in several of the acellular vaccine components, such as ptxP3, prn2, and fim3B, have appeared, and the predominant profile observed no longer completely matches the strains used to make the acellular vaccine components (12)(13)(14)(15).…”
mentioning
confidence: 99%